PENGARUH PEMBERIAN BIOCHAR TERHADAP TANAMAN SAWI HIJAU (BRASSICA JUNCEA L.) PADA LAHAN YANG TERCEMAR LIMBAH CAIR DI SUBAK CUCULAN DESA KEPAON - Semita, I Ketut; Sujana, I Putu; Suryana, I Made (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2017)
This study entitled "The Effect of Type Biochar on Growth and Yield Plant Green Mustard (Brassica juncea L) On The Contaminated Land Wastewater In Subak Cuculan Kepaon village". Field research was conducted in Subak Cuculan Kepaon Village, South Denpasar District for 35 days from the date of December 26, 2016 until January 31, 2017. The study aims to determine the type of biochar most good for the growth and yield of green cabbage grown on land contaminated liquid waste , Research using Random Design (RBD) with 5 treatments, treatment biochar rice husk (B1), biochar chicken manure (B2), biochar coconut (B3), biochar mahogany (B4) and control (B0) of each treatment was repeated 5 times that number to 25. Where all treatments of chicken manure biochar treatment (B2) with a dose of 15 ton / ha gives good results most growth compared with the treatment of other biochar and highly significant (P <0.01) to the control (B0) for all parameters of observations such as plant height maximum, the number of maximum leaf, wet weight of the total crop per plant, fresh weight plant roots per plant, dry weight oven total crop per plant, dry weight oven plant roots per plant and treatment biochar chicken manure (B2) an increase of 35.6% against the results of the parameters total plant fresh weight per plant, and the resulting increase 153.6% to the total oven dry weight of plants per plant compared to the control (B0).